Taxonomic notes on the crab spider genera Stephanopoides and Isaloides (Araneae: Thomisidae: Stephanopinae) - Teixeira, Renato Augusto; Barros, Bruno Augusto Reis (Zootaxa, 2015)
According to current catalogues, two species are allocated to the genus Parastephanops F. O. Pickard-Cambridge, 1900. The examination of the type of Parastephanops cognatus (O. Pickard-Cambridge, 1892) (type-species of Parastephanops) has revealed the presence of a high cephalic region, legs with dark metatarsus and apex of tibia, and triangular epigynum with median ridge, all diagnostic features of Stephanopoides Keyserling, 1880. However, the female of P. echinatus (Banks, 1914) has a low cephalic region, a median ocular quadrangle longer than wide and a large atrium of the epigynum, which are diagnostic features of Isaloides F. O. Pickard-Cambridge, 1900. Thus, Parastephanops is synonymized with Stephanopoides and its two species, P. cognatus and P. echinatus, are redescribed, illustrated and assigned to Stephanopoides and Isaloides, respectively. We also propose that Pyresthesis berlandi Caporiacco, 1947 is a junior synonym of Stephanopoides simoni Keyserling, 1880 based on shape and arrangement of the epigynal plate, copulatory ducts and spermathecae.